Čechořečnost seu grammatica linguae Bohemicae Hrsg. von Jiří Marvan. Nachdruck der Ausgabe Micro-Pragae 1672 - Rosa, Václav J. (Specimina philologiae Slavicae, 1983)
In the history of Czech linguistic theory and thought there is hardly a book more controversial than the grammar of Václav J. Rosa (1620-1689), Čechořečnost seu Grammatica Linguae Bohemicae. It appeared in 1672, two years after Comenius's death, at the beginning of the dark age (temno) which came to symbolize for the revivalist tradition, haunted as it was by the past, the decadence of Czech literature, culture and national spirit. Given this, Rosa's grammar (henceforth RG) was inevitably destined to acquire the stigma of the same degenerate qualities which corrupted the nation's very soul, ist language. Durchsuchbare elektronische Faksimileausgabe als PDF. Digitalisiert im Rahmen des DFG-Projektes Digi20 in Kooperation mit der BSB München. OCR-Bearbeitung durch den Verlag Otto Sagner.